Evaluation of the incidence, risk factors, severity, and outcome of hydrocephalic fetuses in a tertiary healthcare center located in Northern India: a prospective observational study - Garg, Aditi Jain; Najam, Rehana; Agarwal, Ritika; Rastogi, Rajul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Hydrocephalus is a heterogeneous disease marked by abnormal dilatation of the cerebral ventricles secondary to varying etiologies. This study was aimed to determine the incidence, risk factors, severity, and outcome of hydrocephalic fetuses presenting to a tertiary healthcare hospital located in northern India. Methods: In this prospective observational study, pregnant women visiting the obstetrics outpatient department of our hospital from 01 July 2017 to 31 June 2018 were screened for hydrocephalic fetuses via ultrasonography along with a detailed history, and a comprehensive battery of diagnostic investigations. They were followed up for a minimum period of two months after delivery/termination of pregnancy. Results: A total of 3627 pregnant women were screened, of which 10 had hydrocephalic fetuses in the observed time period. The incidence of hydrocephalus was determined to be 2.75 per 1000 live births. Low socio-economic status was identified as a major risk factor. 50% of the hydrocephalic fetuses were severely afflicted and were discontinued. The remaining 50% were successfully delivered and were managed via a ventriculo-peritoneal shunt or are under close observation in the postnatal period without any adverse outcome. Conclusions: The burden of hydrocephalus is considerably high in India, as compared to western countries. In rural settings, low socioeconomic status and lack of folic acid supplementation have a major influence in the etiopathogenesis of hydrocephalus. Management of hydrocephalus requires a multidisciplinary approach and is tailored according to the severity of the presentation. Severe cases of hydrocephalus and cases with associated anomalies have a poor prognosis.